Disturbed bone remodelling activity varies in different stages of experimental, gradually progressive apical periodontitis in rats - Xu, Ruoshi (Int J Oral Sci, 2019)
Bone remodelling keeps going through the lifespan of human by bone formation and bone resorption. In the craniofacial region, mandibles act as the main force for biting and chewing, and also become susceptible to a common bone-loss disease, namely, apical periodontitis, once infected dental pulp is not treated timely, during which bone resorption occurs from the apical foramen to the apical bone area. Although conventional root canal treatment (RCT) can remove the most of the infection, chronical apical periodontitis due to incomplete removal of dental pulp and subsequent microleakage will become refractory and more challenging, and this process has scarcely been specifically studied as a bone remodelling issue in rat models. Therefore, to study chronical and refractory apical periodontitis owing to incomplete cleaning of infected dental pulp and microleackage in vivo, we establish a modified rat model of gradually progressive apical periodontitis by sealing residual necrotic dental pulp and introducing limited saliva, which simulates gradually progressive apical periodontitis, as observed in the clinical treatment of chronical and refractory apical periodontitis. We show that bone-loss is inevitable and progressive in this case of apical periodontitis, which confirms again that complete and sound root canal treatment is crucial to halt the progression of chronical and refractory apical periodontitis and promote bone formation. Interestingly, bone remodelling was enhanced at the initial stage of apical periodontitis in this model while reduced with a high osteoblast number afterwards, as shown by the time course study of the modified model. Suggesting that the pathological apical microenvironment reserve its hard tissue formation ability to some degree but in a disturbed manner. Hopefully, our findings can provide insights for future bone regenerative treatment for apical periodontitis-associated bone loss.